2000
DOI: 10.1073/pnas.97.21.11377
|View full text |Cite
|
Sign up to set email alerts
|

A Ufd2/D4Cole1e chimeric protein and overexpression of Rbp7 in the slow Wallerian degeneration ( Wld S ) mouse

Abstract: Exons of three genes were identified within the 85-kilobase tandem triplication unit of the slow Wallerian degeneration mutant mouse, C57BL͞Wld S . Ubiquitin fusion degradation protein 2 (Ufd2) and a previously undescribed gene, D4Cole1e, span the proximal and distal boundaries of the repeat unit, respectively. They have the same chromosomal orientation and form a chimeric gene when brought together at the boundaries between adjacent repeat units in Wld S . The chimeric mRNA is abundantly expressed in the nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
197
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(203 citation statements)
references
References 30 publications
4
197
0
2
Order By: Relevance
“…Nmnat1 and Wallerian degeneration L Conforti et al as described previously, 14 and mouse monoclonal anti-b-actin (Abcam) was used as a loading control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nmnat1 and Wallerian degeneration L Conforti et al as described previously, 14 and mouse monoclonal anti-b-actin (Abcam) was used as a loading control.…”
Section: Methodsmentioning
confidence: 99%
“…Two antibodies raised against the Wld S protein, 183 and Wld-18, were used to demonstrate expression of Ube4b/Nmnat1 and W258A, as described previously. 8,14 Expression of Nmnat1 was demonstrated with a polyclonal antibody to Nmnat1 (D20 from Santa Cruz Biotech, 1 : 100 concentration).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies showed that the slow Wallerian degeneration phenotype in the Wld S mice is due to the over-expression of an fusion protein Wld S that consists of the amino-terminal 70 amino acids of UFD2, which is an evolutionally conserved protein involved in protein poly-ubiquitination (Koegl et al, 1999), and the nicotinamide mononucleotide adenylyltransferase (Nmnat1) (Conforti et al, 2000). Initially, there was some controversy regarding whether individual fragments of the Wld S gene (UFD2 or Nmnat1), or the entire chimeric gene, are responsible for the phenotypes (Araki et al, 2004;Wang et al, 2005;Zhai et al, 2006;Conforti et al, 2007).…”
Section: Molecular Mechanisms Of Wld S -Mediated Protectionmentioning
confidence: 99%
“…Perhaps the Nmnat1 expressed in transgenic mice generated by Conforti (Conforti et al, 2007) did not reach a high level and still primarily localized in the nucleus; therefore, insufficient amounts of Nmnat1 were available in the axons for the protective effects. In addition, although many reports suggest that Wld S is localized to the nucleus of neurons in the Wld S mice (Coleman, 2005), all of these studies relied on an antibody prepared against an 18-amino acid peptide in Wld S (between UFD2 and Nmnat1) (Conforti et al, 2000;Fang et al, 2005). UFD2 itself localizes to both the nucleus and axons (Fang et al, 2005), and thus the fusion protein Wld S might be brought to axons by the UFD2 fragment.…”
Section: Molecular Mechanisms Of Wld S -Mediated Protectionmentioning
confidence: 99%